FEATURES OF RISK REFLECTION IN INTEGRATED REPORTING - KARPUSHENKO, MARIYA; FILATOVA, IRINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The issue of identifying and measuring business risks is extremely important for today’s business, because under any circumstances there may be a situation that will negatively affect the company and lead to unexpected financial consequences. All this requires the creation of an effective risk management system that would identify, anticipate and measure risks. It should be emphasized that there are certain rules and standards in accounting that allow you to pre-assess business risks. Therefore, to create such a system it is necessary to combine accounting standards and risk management principles. The risk management process involves identifying risks associated with business activities; assessment of information needed to identify risks; the choice of methods for assessing the probability of occurrence of a risky event; determining the amount of possible financial losses in the event of a risky event; comparison of the amount of damage with the criterion of materiality; reflection of accounting risks; choice of methods of internal risk neutralization. In modern conditions, the company is constantly faced with different types of risks during its activities. Therefore, the problem of identifying and reflecting risks is extremely relevant. The purpose of the article is to consider the issues of risk assessment and reflection. The types of risks depend on many circumstances and problems that the company actually faces. The reflection of risks in accounting involves the creation of certain funds, reserves, provision and recording of information about risk events in integrated reporting. The problem of identification, measurement and assessment of risks is extremely relevant, because in modern conditions, companies may have situations that are characterized by risks. Risk management is a rather complex process, which depends on its types and includes the procedure of certain actions and the use of methods for assessing possible losses. For enterprises, it is necessary to measure, assess the feasibility of reflection and reflect risks in integrated reporting. Further research should pay attention to the process of measuring and assessing risks.